Systematic Review: Histological Scoring of Strictures in Crohn's Disease. (22nd June 2020) - De Voogd, F A; Mookhoek, A; Gecse, K B; De Hertogh, G; Bemelman, W A; Buskens, C J; D'Haens, G R
Abstract: Background and Aims: In Crohn's disease, many patients develop a stricture, which can due to inflammation, fibrosis and muscular changes or all at the same time. Determining the predominant component has therapeutic consequences but remains challenging. To develop imaging techniques that assess the nature of a stricture, a gold standard is needed and histopathology is considered as such. This paper provides an overview of published histological scoring systems for strictures in Crohn's disease. Methods: A systematic literature review according to PRISMA guidelines was performed of histological scoring indices that assessed whether a stricture was inflammation-predominant or fibrosis-predominant. Multiple libraries were searched from inception to December 2018. Two reviewers independently assessed abstracts and full-texts. Results: Sixteen articles were identified as suitable for this systematic review. A large number of parameters were reported. Extent of neutrophil infiltration and extent of fibrosis in the bowel wall were most frequently described to reflect severity of inflammation and fibrosis, respectively. Among the 16 studies, only two described a numerical scoring system for the inflammatory and fibrotic component separately. Smooth muscle changes were scored in a minority of studies. Conclusions: Multiple scoring systems have been developed. There was large heterogeneity in scoring per parameter and construction of numerical scoring systems. Therefore, we feel that none of the systems is suitable to be used as gold standard. We offer an overview of histological parameters that could be incorporated in a future histological scoring index for strictures.